1992
DOI: 10.1002/mds.870070209
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to well water and pesticides in Parkinson's disease: A case‐control study in the madrid area

Abstract: Past exposure to well water and pesticides was assessed in 128 unselected Parkinson's disease (PD) patients and 256 age and sex-matched controls. All were residents in a defined urban area of Madrid, Spain. In keeping with other reports, we found that exposure to well water might be a factor associated with the likelihood of developing PD, though only prolonged exposures of 30 years or longer were significantly different between PD and controls (p less than 0.02). In contrast, past exposure to pesticides did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 16 publications
2
30
1
1
Order By: Relevance
“…Drinking water from a private well has been implicated in the development of PD in some studies [11,13,21]. We did not observe any statistical increase in the risk of PD associated with ingesting well, bore or spring water.…”
Section: Discussionmentioning
confidence: 44%
“…Drinking water from a private well has been implicated in the development of PD in some studies [11,13,21]. We did not observe any statistical increase in the risk of PD associated with ingesting well, bore or spring water.…”
Section: Discussionmentioning
confidence: 44%
“…Some epidemiological investigations have suggested that increased exposure to agricultural chemicals via living in a rural environment, drinking well water, or occupational exposure may be a potential environmental risk factor for the disease (3)(4)(5)(6)(7)(8)(9). The widely used herbicide paraquat has been demonstrated to selectively damage the nigrostriatal dopaminergic system (11) and exposure to this specific agricultural chemical has been postulated to be a prime risk factor for PD (3,7).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have suggested that exposure to agricultural chemicals is associated with an increased risk of developing PD (3)(4)(5)(6)(7)(8)(9). The herbicide 1,1Ј-dimethyl-4,4Ј-bipyridium (paraquat, PQ) may contribute to the pathogenesis of PD based on both epidemiological studies of parkinsonism correlated with exposure to the agent (3,7), and its structural similarity to the active metabolite of the parkinsonism-inducing agent 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine, 1-methyl-4-phenylpyridium ion.…”
Section: Parkinson Disease (Pd)mentioning
confidence: 99%
“…One study reported an OR of 7.0 (p value <0.05) [289] and another an OR of 10.9 (95% CI 2.5-48.0) [301]. The remaining 19 case-control studies that analyzed results from pesticide exposure overall reported no association [131,136,137,141,142,144,145,[305][306][307][308][309][310][311][312][313][314][315][316][317].…”
Section: Case-control Studiesmentioning
confidence: 99%